Minimising embodied carbon in reinforced concrete flat slabs through parametric design. (1st June 2022) - Jayasinghe, Amila; Orr, John; Ibell, Tim; Boshoff, William P.
Abstract: Minimising carbon emissions from the building construction industry is of paramount importance in the present context due to the rising concerns of climate change. This paper explores the potential of minimising embodied carbon in reinforced concrete flat slabs by parametrically varying the slab thickness, grade of concrete, column spacing, column size, and reinforcement details. A parametric design algorithm was developed to generate a range of one storey structural frames with flat slabs and to calculate their 'cradle-to-gate' embodied carbon per unit floor area while identifying the viable design space and relevant limiting criteria. Also, a parametric finite element model is parallelly developed to estimate non-linear long-term deflection and to investigate the possibility of further reducing embodied carbon by scrutinising the deflection related design limits. The effect on the optimum designs by the adopted carbon coefficients is also quantified. The flat slab design with minimum embodied carbon for a given design load and column spacing corresponds to the minimum allowable thickness, largely insensitive to adopted carbon coefficients. Relaxing the deflection limit can reduce embodied carbon but only by around 20% of the required percentage increase in the deflection. The possibility of reducing embodied carbon by providing more reinforcement to further reduce slab depths allowed by the deflection criteria is sensitive to the adopted carbon coefficients. Minimising embodied carbon in flat slabs require optimising column spacing, using lower grades of concrete, and minimising slab depth based on deflection checks. Highlights: Variation of embodied carbon in flat slabs with design parameters are illustrated. Parametric design with deflection checks can save embodied carbon up to 8%. Lower grades of concrete can reduce carbon up to 12% even with thicker slabs. The optimum designs coincide with minimum allowable thickness in most of the cases.